Pengaruh Wudhu Bagi Kesehatan Tubuh, Gigi, dan Mulut - Siti Habibah; Andini Eka Putri; Aisha Luthpia (Pusat Riset dan Inovasi Nasional, 2023)
Wudhu is one way of purifying a small limb of hadast and an ordinance before performing prayers. This article uses qualitative methods that contain results and discussions covering wudhu, dalil the qur 'an and the hadist definitions of wudhu, and the influence of wudhu to health of the body, teeth, and mouth. It turned out that wudhu was not just a way to sanctify himself before performing the worship of prayer, but wudhu had the lessons and benefits in it. The value of wudhu in health is to clean away areas of the body that are frequently exposed to things or things that are contaminated with droppings, viruses, or bacteria. For example, such as dust on the face, teeth and mouth used for eating and drinking, hands used to handle objects or do things on them and so forth. Sometimes we don't realize that what we consider clean is actually something dirty and can be a source of illness. So that we can understand that berating not only as a ritual before engaging in pure worship but also has the benefit of preventing contamination, viruses, or bacteria from propagating in the body so that berating can prevent a variety of mild diseases to severe diseases.